Carte de la province de Québec, Canada - Taché, Eugène-Etienne, 1836-1912 (Surveyor); The Burland Lithographic Company (Lithographer) (Crown Lands Department Canada, 1880)
This is a map of administrative divisions in the province of Quebec in 1880, extending from the American border to the south to Lake Mistassini to the north, and from the Ontario border to the west to Anticosti Island to the east. It shows districts, lordships, counties, townships, cities, railways, canals, roads and boundaries. It includes a longitude-latitude table and inset of Northeastern Quebec. In French. Scale approximately 1:633,360. Relief shown by hachures. Shows districts, lordships, counties, townships, cities, railways, canals, roads and boundaries. Includes a longitude-latitude table and inset of Northeastern Quebec. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .